2022
DOI: 10.1021/acs.langmuir.2c00836
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme is Sterically Trapped Within the Silica Cage in Bioinspired Silica–Lysozyme Composites: A Multi-Technique Understanding of Elusive Protein–Material Interactions

Abstract: Lysozyme is widely known to promote the formation of condensed silica networks from solutions containing silicic acid, in a reproducible and cost-effective way. However, little is known about the fate of the protein after the formation of the silica particles. Also, the relative arrangement of the different components in the resulting material is a matter of debate. In this study, we investigate the nature of the protein–silica interactions by means of solid-state nuclear magnetic resonance spectroscopy, small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…The same authors used time-resolved SAXS to characterize the early phases of the polymerization and concluded that the protein unfolds significantly and only partly regains its structure in the final composite [20]. However, we and others have found by 13 C solid-state magic angle spinning NMR, which bears intrinsically higher resolution information on the state of the protein component, that the protein fold is not significantly altered in the composite [21][22][23]. We then tested the behavior of the composite with respect to washing, and we found, in line with Luckarift et al, that the protein is not washed away from the material using water.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…The same authors used time-resolved SAXS to characterize the early phases of the polymerization and concluded that the protein unfolds significantly and only partly regains its structure in the final composite [20]. However, we and others have found by 13 C solid-state magic angle spinning NMR, which bears intrinsically higher resolution information on the state of the protein component, that the protein fold is not significantly altered in the composite [21][22][23]. We then tested the behavior of the composite with respect to washing, and we found, in line with Luckarift et al, that the protein is not washed away from the material using water.…”
Section: Introductionmentioning
confidence: 77%
“…Thus, the interaction between the protein and the material concerns both the outer surface of the material but also the surface of the inner structural components of silica. From the analysis of { 1 H}-13 C HETCOR and { 1 H}- 29 Si HETCOR [24][25][26] spectra acquired on the composite [23,27], we could prove that lysozyme remains in tight contact with surface 29 Si species of condensed silica, but it is not covalently bound, as opposed with what is observed in the case of the polycationic peptide PL12 [28]. However, the molecular details of this interaction remain elusive.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Their presence on the surface makes it nonpolar, which makes the precursor hydrophobic. Its consequence is poor solubility in aqueous solutions and lack of contact with biomacromolecules and cells, which is needed for their mineralization [ 53 , 81 , 82 , 83 ];…”
Section: Chemistry Of Sol–gel Processesmentioning
confidence: 99%
“…Immobilization by means of a two-stage scheme has been applied in many laboratories, showing its effectiveness. It was successfully used to entrap alkaline and acid phosphatase [ 217 , 222 , 229 ], bacteriorhodopsin [ 74 ], butyrylcholinesterase [ 218 ], cholesterol oxidase and cholesterol esterase [ 230 ], cyclodextrin [ 231 ], cytochrome c [ 49 , 232 , 233 , 234 ], DNA [ 219 , 235 ], glucose-oxidase [ 184 , 236 , 237 ], horseradish peroxidase [ 87 , 232 , 238 , 239 , 240 ], lipase [ 157 , 241 ], lysozyme [ 82 , 83 , 242 , 243 ], myoglobin [ 49 , 242 ], RNA aptamers [ 66 ] tryptophan [ 244 ], tyrosinase [ 239 ]. In addition, the method has been used to immobilize bacteria [ 88 , 196 , 222 , 224 , 225 , 245 , 246 ], microalgae [ 44 , 227 ], and viruses [ 228 ].…”
Section: Biomimetic Approachesmentioning
confidence: 99%